'Doing the Alexander': On Christmas motifs in Bergman's Fanny and Alexander. Issue 3 (1st September 2013) - Steene, Birgitta
This short subject examines Christmas motifs in Ingmar Bergman's film Fanny and Alexander with particular emphasis on autobiographical, literary and ethnographic roots, and explores visual and psychological themes defining the contrasting lifestyles of the Ekdahl and Vergérus households: joie de vivre vs rigid moralism; sensuality vs asceticism; light vs darkness; magic vs stark realism; and theatrical performance vs church dogma.